POLA KONSENTRASI SPASIAL INDUSTRI KECIL MENENGAH DI PROVINSI NUSA TENGGARA BARAT - CHANDRADITYA BAGASKARA; PUTU KARISMAWAN; FIRMANSYAH FIRMANSYAH (GANEC SWARA, 2021)
Location Theory gives systematic analysis framework  of selecting location of economic adn social activities. Chosing of the right location  thrifts reduce the transportation and production cost that drives efficient in production and marketing. The impact of efficiency is the higest profit and concentration of economic activities. There are many factor afecting the concentration of economic activities, such as wages, man power sources and productivity. Based on Concentration Ratio analysis that Small-medium  industries cosentrated in Mataram City and Central Lombok distric. Based on concentration Index of Man power  shows that the concentration of man power  are in Sumbawa district, North Lombok, Central Lombok, Bima City, Bima district and West Lombok district. Based on those  result that concentration spatial of Small-Medium Industries in each district of West Nusa Tenggara are not equal . Based on Regresioan analysis with Randomeffect Model that concentration of small-medium industries in West Nusa Tenggara siginificanly corelated with amount of man power and productivity, neither than wages.